ON OPIUM POPPY BREEDING AND TRADE IN ANATOLIA - Filiz ÇOLAK (Fırat University, 2019)
A variety of medical and industrial plants have been planted in the rich Anatolian soil for thousands of years. One of these plants is opium poppy, mostly known for opium extracted from the milky juice in the seed capsules of the plant. Opium (afyon) has been so widely known and significant for the people of Anatolia that one of the cities where it has been produced was named for the plant. As a sought after industrial raw material, opium has been planted in Anatolia since the time of the Hittite Empire (c. 2000 BC). Since Anatolian opium contains considerably more morphine than those of other breeding areas throughout the world, it has become a material highly in demand in the global market. Therefore, opium poppy hasn’t been intended to cover local needs only and it has been considered, almost totally, as a cash crop. During the nineteenth century, opium poppy was recorded as the seventh biggest cash crop in the Ottoman State, following tobacco, wheat, barley, raisin, fig and raw silk. The importance given to opium trade during the Ottoman State continued in the Turkish Republic. However in this period the state sometimes imposed restrictions on opium planting. In 1933 opium poppy cultivation was brought under state control, growing areas were restricted and cultivation was only allowed in 17 counties. Due to increase in need and demand for opium and opium oil during the Second World War, opium poppy growing areas were expanded with a decree issued on June 16, 1945 and 35 counties were allowed in Turkey for opium poppy cultivation. However as the conditions changed, opium poppy growing areas were again narrowed. In 2011, opium poppy cultivation was carried out in 13 cities and growing areas were 54.911 hectares. This study aims to analyze the crop inventory and export activities of opium poppy in Anatolia from the Ottoman State to the Turkish Republic.